Modelling mine gas explosive pattern in underground mine gob and overlying strata. (6th November 2019) - Cheng, Jianwei; Qi, Chang; Li, Siyuan
A 3D physical experimental model is well designed to simulate a U-type underground mine working face. Based on two important influence factors, the air quantity delivered into the ventilation system and the gas release rate (GRR) in gob, a series of experiments are designed to examine the range pattern of gas explosive zone changing in the mine gob with following various combinations of air velocities and GRRs. By sampling works, the gas concentration could be obtained at different horizontal levels and vertical lines in the experiment model. The experimental results show various shapes and areas of explosive zones in gob and in overlying caved spaces as the GRR and air velocities change. This research work is of great reference for mining engineers to apply the ventilation design practices to minimise the explosion hazard risk in a mine gob area. [Received: July 26, 2017; Accepted: December 13, 2017]